2018
DOI: 10.1016/j.bjorl.2017.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Degree of tinnitus improvement with stapes surgery – a review

Abstract: We conclude that stapes surgery is effective for the treatment of tinnitus (average improvement is 85.52%), and hearing loss (average improvement is 93%). When deciding about the surgical indication in patients with otosclerosis, the presence and level tinnitus should be considered as well as the level of hearing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 11 publications
(4 reference statements)
1
10
0
3
Order By: Relevance
“…In a study by Cavalcante et al, done as a review of articles, eight papers were investigated on the tinnitus improvement after the stapes surgery. The degree of postoperative tinnitus improvement during this examination was reported 85.52% [16]. In the present study, 84.4% of patients noted the postoperative tinnitus improvement.…”
Section: Discussionsupporting
confidence: 57%
“…In a study by Cavalcante et al, done as a review of articles, eight papers were investigated on the tinnitus improvement after the stapes surgery. The degree of postoperative tinnitus improvement during this examination was reported 85.52% [16]. In the present study, 84.4% of patients noted the postoperative tinnitus improvement.…”
Section: Discussionsupporting
confidence: 57%
“…Audiological evaluation of tinnitus and evidence-based interventions require the evaluation of both tinnitus perception and individual reactions to it, which can obtained using a validated questionnaire [ 12 ]. A recent review on the impact of stapes surgery on tinnitus severity revealed that only a few scientific papers have been published that include self-report tools in the evaluation of tinnitus severity [ 20 ]. For example, Dewyer et al [ 32 ] and Chang and Cheung [ 33 ] used the TFI questionnaire to measure tinnitus severity.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few publications focusing on the assessment of tinnitus in otosclerosis have been published [ 20 ]. The majority of studies have been carried out retrospectively and have all the limitations associated with this type of study.…”
Section: Introductionmentioning
confidence: 99%
“…El 73 % de los pacientes informaron una mejoría en el tinnitus luego de la estapedectomía, compartiendo ésta tasa de éxito con numerosas otras investigaciones (24,25) y, simultáneamente, más del 85 % indicaron que su audición mejoró. Estos resultados positivos en la audición eran esperados, ya que es el objetivo principal de la estapedectomía.…”
Section: -72discusiónunclassified